Le lent dévoilement du travail des agricultrices - Christian Nicourt (Éditions en environnement VertigO, 2014)
This article accounts for the slow unveiling of the importance of female work on the farms. It aims at understanding why the work of women on the farms has generally been denied and has remained invisible, and why it may become visible in certain situations. It contends that the invisibilization as well as the visibilization of female work on the farm result largely from the way women gain access to this profession and from how the organization of the work on the farm. The article investigates the work of thirty women farmers of two French regions, Britanny and Aquitaine. It first examines their professional careers. Then it analyzes how these female farmers organize their work. Finally it highlights the consequences of their ways of working on the ways they define their professional identity.